An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Distinct patterns of intestinal microbiota and immune responses under acute and chronic ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Kun Xiao; Liling Nie; Shasha Zhao; Gehan Gao; Cuancheng Zhao; Yanjun Du; Rongfei Hu; Ruru Lin; Jie Wang; Man Wang; Dong Han; Lei Zhang (Aquaculture, 2026)

Antimony exposure promotes cardiac fibrosis via lactate-mediated cardiomyocyte-fibroblast crosstalk: A novel Sirt1-glycolysis axis - Xin Li; Zhenzhen Dai; Xiaoyong Ren; Hao Zhao; Lirong Chan; Ruotong Wu; Xinyi Xiao; Qiao Liu; Liling Su (Journal of Environmental Sciences, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Removal of PFAS and 1,2,4-TCB from firefighting-contaminated sites by iron-modified biochar microspheres loaded with microbes - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuan Jiang; Yipin Geng (Journal of Cleaner Production, 2026)

Unraveling the Low Residual Mechanism of Polycyclic Aromatic Hydrocarbons in Rice Grains Driven by Low Moisture Regulation: Microbial Mediated Health Effects - Zhenhua Zhao; Xiaorou Wang; Yueli Liu; liling Xia; Zhirui Qin; Jingjing Cao; Harry Toland (Journal of Soil Science and Plant Nutrition, 2026)

Multilayered regulatory control of compound leaf development - Liangliang He; Liling Yang; Weiyue Zhao; Jianghua Chen (Current Opinion in Plant Biology, 2026)

Study on PFAS removal by different forms of iron-modified biochar: Adsorption effects and catalytic activity - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Jiayuan Cheng; Wenqing Zhang; Hailong Wang (Journal of Environmental Chemical Engineering, 2025)

Ontogenetic niche segregation and its implications for mercury levels in Japanese anchovy from the high seas of the northwestern Pacific Ocean as revealed by fatty acid analysis - Long Chen; Zhenfang Zhao; Guanyu Hu; Liling Zhang; Bilin Liu; Xinjun Chen (Journal of Fish Biology, 2025)
Japanese anchovy ( Engraulis japonicus ) is a small pelagic fish that is frequently targeted by commercial fisheries. Japanese anchovy plays a crucial role as a vital link between primary and higher‐order consumers. The elemental mercury in Japanese anchovy muscles easily bioaccumulates and is transmitted to top predators. We investigated the variation in the diets and mercury accumulation of Japanese anchovy in the high seas of the northwestern Pacific Ocean. We measured the amounts of mercury and fatty acids in the muscles of 149 Japanese anchovy specimens that were obtained from the open seas of the northwestern Pacific Ocean (39°2′ N ~ 42°30′ N, 154°02′ E ~ 161°29′ E) between June and July 2021. The results revealed that the monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) contents significantly decreased and then increased with the growth of Japanese anchovy ( p

Study on the effect of alginate coated Ca-Fe bimetallic composite biochar microspheres on the removal of short-chain PFAS - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Hailong Wang; Olive M. Yemele; Muhammad Adnan (Environmental Research, 2025)

Tailored synthesis of heterojunction CuNTiO2 and g-C3N4 composite for advanced degradation of 1,2,4-trichlorobenzene under visible light - Olive Mekontchou Yemele; Zhenhua Zhao; Ervice Ymele; Abduelrahman Adam Omer; Muhammad Usman; Liling Xia; Cedric Karel Fonzeu Monguen; Teng Binglu; Franck Ghislain Emani (Journal of Water Process Engineering, 2025)

Unraveling microbial assembly and co-occurrence relationship at seasonal and vertical scales in an aged organic-contaminated site - Zhirui Qin; Zhenhua Zhao; Liling Xia; Jiayuan Liu; Xuan Li; Aiwei Zhang; Yue Wang; Jingwei Wang (International Biodeterioration & Biodegradation, 2025)

A global systematic review and meta-analysis of innovative technologies for 1,2,4-trichlorobenzene remediation in soil and water - Olive Mekontchou Yemele; Zhenhua Zhao; Mbezele Junior Yannick Ngaba; Ervice Ymele; Liling Xia; Wang Xiaorou; Prince Atta Opoku (Environmental Geochemistry and Health, 2025)

Role of heat pretreatment and transglutaminase treatment on the gelling properties of pea protein - Suqi Yang; Liling Tao; Zihang Yan; Kefan Ouyang; Qin Zhang; Yuanyuan Feng; Qiang Zhao (Food Bioscience, 2025)

Microbiologically influenced corrosion inhibition of carbon steel by a novel bacterium, Photobacterium sp., in simulated marine environment - Tingting Zhu; Liling Xu; Lijing Yang; Pingping Zhao; Xinglong Zhu; Zhengli Wu; Zhenlun Song (Environmental Research, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Progress on the removal of PFAS contamination in water by different forms of iron-modified biochar - Binglu Teng; Zhenhua Zhao; Liling Xia; Jiangxuan Wu; Hailong Wang (Chemosphere, 2024)

The role and regulation of SIRT1 in pulmonary fibrosis - Xinyi Ma; Mengna Jiang; Wenqian Ji; Mengjiao Yu; Can Tang; Kai Tian; Zhengnan Gao; Liling Su; Juan Tang; Xinyuan Zhao (Molecular Biology Reports, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Effects of diet and habitat on Hg levels in Japanese anchovy in the high seas of the northwestern Pacific Ocean - Long Chen; Guanyu Hu; Zhenfang Zhao; Bilin Liu; Xinjun Chen; Liling Zhang (Marine Pollution Bulletin, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

First report of chilli veinal mottle virus infecting Lactuca sativa in China - Yue Chen; Gui Gao; Ting Ting Li; Jie Chen; Yue Yan Yin; Jing Zhong; Liling Zhao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

Multi-omics analysis provides insight into liver metabolism in yellow catfish (Pelteobagrus fulvidraco) under hypoxic stress - Man Wang; Shasha Zhao; Jie Wang; Liling Nie; Li Li; Xiaoming Zhu; Lei Zhang (Aquaculture, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Arthrospira cell residue valorization: A study on protein hydrolysate production by limited enzymatic hydrolysis - Kefan Ouyang; Qian Chen; Hexiang Xie; Qin Zhang; Liling Tao; Hua Xiong; Yulan Du; Jiangang Yan; Xinliang Mao; Qiang Zhao (Food Bioscience, 2023)

Vertical and seasonal dynamics of bacterial pathogenic communities at an aged organic contaminated site: Insights into microbial diversity, composition, interactions, and assembly processes - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Zijun Yang (Journal of Hazardous Materials, 2023)

Significant roles of core prokaryotic microbiota across soil profiles in an organic contaminated site: Insight into microbial assemblage, co-occurrence patterns, and potentially key ecological functions - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Yuhong Liu (Environmental Research, 2023)

The ecological response and distribution characteristics of microorganisms and polycyclic aromatic hydrocarbons in a retired coal gas plant post-thermal remediation site - Zhenhua Zhao; Barry Mody Oury; Liling Xia; Zhirui Qin; Xiangyu Pan; Jichan Qian; Fangzhou Luo; Yong Wu; Luqi Liu; Wei Wang (Science of The Total Environment, 2023)

Research trends and hotspots of aquatic biofilms in freshwater environment during the last three decades: a critical review and bibliometric analysis - Zhirui Qin; Zhenhua Zhao; Liling Xia; Okugbe Ebiotubo Ohore (Environmental Science and Pollution Research, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

Cu/N-codoped TiO2 prepared by the sol-gel method for phenanthrene removal under visible light irradiation - Zhenhua Zhao; Abduelrahman Adam Omer; Zhirui Qin; Salaheldein Osman; Liling Xia; Rajendra Prasad Singh (Environmental Science and Pollution Research, 2020)

Correction to: Cu/N-codoped TiO2 prepared by the sol-gel method for phenanthrene removal under visible light irradiation - Zhenhua Zhao; Abduelrahman Adam Omer; Zhirui Qin; Salaheldein Osman; Liling Xia; Rajendra Prasad Singh (Environmental Science and Pollution Research, 2019)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)

Complete genome sequence of a new bipartite begomovirus infecting Boehmeria leiophylla in China - Liling Zhao; Jing Zhong; Xiaoyun Zhang; Ming Ding; Zhongkai Zhang (Archives of Virology, 2018)

Two distinct begomoviruses associated with an alphasatellite coinfecting Emilia sonchifolia in Thailand - Liling Zhao; Jing Zhong; Xiaoyun Zhang; Yueyan Yin; Tingting Li; Ming Ding (Archives of Virology, 2018)

Soil heavy metal pollution and risk assessment associated with the Zn-Pb mining region in Yunnan, Southwest China - Xianfeng Cheng; Tomas Danek; Jarmila Drozdova; Qianrui Huang; Wufu Qi; Liling Zou; Shuran Yang; Xinliang Zhao; Yungang Xiang (Environmental Monitoring and Assessment, 2018)

Application of canonical correspondence analysis to determine the ecological contribution of phytoplankton to PCBs bioaccumulation in Qinhuai River, Nanjing, China - Zhenhua Zhao; Ying Jiang; Liling Xia; Tengfei Mi; Wenming Yan; Yanzheng Gao; Xin Jiang; Elchico Fawundu; Javid Hussain (Environmental Science and Pollution Research, 2014)

Understanding the patterns and mechanisms of urban water ecosystem degradation: phytoplankton community structure and water quality in the Qinhuai River, Nanjing City, China - Zhenhua Zhao; Tengfei Mi; Liling Xia; Wenming Yan; Ying Jiang; Yanzheng Gao (Environmental Science and Pollution Research, 2013)

Characterization of an efficient catalytic and organic solvent-tolerant azoreductase toward methyl red from Shewanella oneidensis MR-1 - Yuyi Yang; Liling Lu; Fen Gao; Yuhua Zhao (Environmental Science and Pollution Research, 2013)

Optimization of extractants, purifying packings, and eluents for analytical extraction of organochlorine pesticides in Hydragric Acrisols - Zhenhua Zhao; Liling Xia; Fang Wang; Xin Jiang; Yanzheng Gao (Environmental Monitoring and Assessment, 2012)